Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah PT. Bank Tabungan Negara (Persero) Tbk Kantor Cabang Sutomo Padang - Fauzan Fauzan; SonyaFutri Ramafina (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine services that include tangible, empathy, reliability, responsibility and assurance on customer satisfaction. This research was conducted at Bank Sutomo Padang Branch Office. The population of this study was 71,600 customers. Meanwhile, the sample from this research was 123 customers. This research is quantitative research and the data analysis method uses multiple linear regression. The results of this research show that the tangible, empathy, responsibility and assurance variables have a positive effect on customer satisfaction, with each calculated t value being greater than the t table and the significant value being smaller in alpha. Meanwhile, the reliability variable does not have a positive and significant effect because the calculated t value is smaller than the t table and the significant value is greater than alpha. The conclusion is that the first hypothesis is accepted, the second hypothesis is accepted, the third hypothesis is rejected, the fourth hypothesis is accepted, and the fifth hypothesis is accepted.